Effect of sources and levels of nitrogen on irrigated sugarcane - Faria, Clementino Marcos Batista de; Morgado, Luiz Balbino; Pereira, José Ribamar; Aragão, Otávio Pessoa (Pesquisa Agropecuaria Brasileira, 2014)
The effect of sources and levels of nitrogen on sugarcane (Saccharum Officinarum L.) yield was studied on a Vertisol in the Sub-Middle São Francisco River valley. The experiment had fourteen treatments consisting of 0, 40, 80, 120, 160 and 200 kg N/ha applied in the form of urea; 40, 80, 120, 160 and 200 kg N/ha applied in the form of ammonium sulphate; and 40, 80,120 and 160 kg N/ha applied in both forms, 50% as urea at planting and the remaining 50% as ammonium sulphate 120 days after planting. The study was conducted in a randomized complete block design with three replications. The results indicated that the effect was the same from the two sours of nitrogen, but there was a highly significant increase in yield as the levels of nitrogen increased. The economical level was 213 kg N/ha. The nitrogen concentration in leaves showed a significant positive and linear correlation with the levels of nitrogen applied and cane yield. Levels of nitrogen did not affect the sugar concentration in the cane.